Evaluation of transient effects in the pressure-time method. (August 2019) - Saemi, Simindokht; Sundström, L.R. Joel; Cervantes, Michel J.; Raisee, Mehrdad
Abstract: The pressure-time is a method for measuring the flow rate in closed conduits and is typically used in hydropower applications. The scope of the present paper is to examine the physics of flow during a pressure-time measurement using experimental data and two-dimensional numerical simulations. The Unsteady Reynolds-averaged Navier–Stokes (URANS) equations coupled with the low-Re k-ω SST turbulence model are employed for the simulations. The contributions of inertia, pressure gradient, viscous and turbulent shear stress terms are investigated in the flow during a pressure-time measurement. It is shown that away from the wall and in the initial moments of time, the turbulent shear stress is comparable with the pressure gradient. With increasing time, the contribution of the inertia term becomes progressively significant and comparable with the pressure gradient and turbulent shear stress terms. Close to the wall, both viscous and turbulent shear stresses are the dominant terms which are diminished by increasing the time. Highlights: Dominant forces in time dependent decelerating flow are inertia, viscous and turbulent shear stresses and pressure gradient. The relative importance of the forces are changing during the deceleration of the flow. At the first times, the turbulent shear stress and pressure gradient are the dominant terms and comparable to each other. By increasing the deceleration rate, the inertia effect is comparable with the pressure gradient and turbulent shear stress. At the final times of the valve closure, both inertia and pressure gradient terms are dominant in the flow.